Normal tissue dose and risk estimates from whole and partial breast radiation techniques. Issue 7 (26th December 2019) - Dutta, Sunil W.; Aliotta, Eric; Alonso, Clayton E.; Bliley, Roy C.; Romano, Kara D.; Libby, Bruce; Showalter, Timothy N.; Showalter, Shayna L.; Janowski, Einsley M.
Abstract: Purpose: To compare radiation dose to organs at risk in patients with early‐stage breast cancer treated with lumpectomy and intraoperative radiation therapy with CT‐guided HDR brachytherapy ( precision breast IORT; PB‐IORT) and those treated with external beam whole breast irradiation (WB‐DIBH) or partial breast irradiation (PB‐DIBH) with deep inspiratory breath hold. Methods: We retrospectively identified 52 consecutive patients with left‐sided breast cancers treated with either PB‐IORT (n = 17, 76% outer breast) on a phase I clinical trial, adjuvant PB‐DIBH (n = 18, 56% outer breast, 6% cavity boost), or WB‐DIBH (n = 17, 76% outer breast, 53% with lumpectomy cavity boost). Conventional (2 Gy/fraction) or moderate hypofractionation (2.66 Gy/fraction) was prescribed for the external beam cohorts and 12.5 Gy in 1 fraction to 1 cm from the balloon surface was prescribed to the HDR brachytherapy cohort. CT‐based planning was used for all patients. Organ at risk doses and excess risk ratios (ERR) for secondary lung cancers, contralateral breast cancers, and cardiac toxicity were compared between treatment techniques. Results: Compared to WB‐DIBH and PB‐DIBH, PB‐IORT resulted in lower ipsilateral lung V5, V10, V20, mean, and max dose ( P < .05). Mean ipsilateral lung BED3Gy was as follows: 1.32 Gy for PB‐IORT, 4.33 Gy for WB‐DIBH, 3.35 Gy for PB‐DIBH. The ERR for lung cancer was lowest for PB‐IORT ( P < .001). There was significantly higher contralateral breast max dose but lower mean BED3Gy for WB‐DIBH compared with PB‐IORT ( P = .012, P = .011, respectively). Mean contralateral breast BED3Gy was as follows: 0.10 Gy for PB‐IORT, 0.06 Gy for WB‐DIBH, and 0.08 Gy for PB‐DIBH. The ERR for contralateral breast cancer was low for all breast techniques, but WB‐DIBH showed lower ERR compared to PB‐IORT ( P = .019). Mean heart BED2Gy was higher with PB‐IORT at 1.26 Gy compared to 0.48 Gy and 0.24 Gy for WB‐DIBH and PB‐DIBH, respectively ( P < .001). Conclusions: Patients with early‐stage breast cancer treated with PB‐IORT and with tissue‐sparing external beam techniques all received low organ at risk doses, but PB‐IORT resulted in far lower ipsilateral lung dose compared with external beam techniques. Our data indicate the lowest mean contralateral breast BED in the WB‐DIBH group, likely due to the simplicity of the field design in low‐risk patients using tangential whole breast radiation. External beam using DIBH results in lowest heart dose, but all techniques were well within recommended heart constraints.